La evaluación ausente. Absent Assessment - Pablo E. Balonga (Arizona State University, 2003)
Absent elements in the evaluation processes of science and technology activities in Buenos Aires University are discussed. The main deficiencies identified are shown to be linked to the organization of the technological scientific system and to inherent conceptions of the scientists. Remedies are analyzed. Absent elements in the evaluation processes of science and technology activities in Buenos Aires University are discussed. The main deficiencies identified are shown to be linked to the organization of the technological scientific system and to inherent conceptions of the scientists. Remedies are analyzed.